Moisture sorption isotherms of fresh and blanched pumpkin (Cucurbita moschata) - Molina Filho, Lucidio [UNESP]; Rebes Goncalves, Ana Karla [UNESP]; Mauro, Maria Aparecida [UNESP]; Frascareli, Elen Cristina [UNESP] (Soc Brasileira Ciência Tecnologia Alimentos, 2011)
Moisture desorption isotherms of fresh and heat blanched pumpkins ( Cucurbita moschata) were determined at three temperatures ( 30, 50 and 70 degrees C), using the standard, static-gravimetric method. The GAB, Oswin, BET, Halsey, and Henderson models were tested and, with the exception of the Henderson model, showed satisfactory fits to the experimental data. The GAB model was used to analyze the fitting ability to describe the isotherm type. The shape of the desorption isotherms of fresh and blanched pumpkin at 30 and 50 degrees C was intermediate to types II and III, and at 70 degrees C it was of type II for the blanched pumpkin and close to type II for the fresh sample. The influence of blanching on the decrease in equilibrium moisture was very small compared to the fresh samples and it was related to the loss of soluble solids during the pre-treatment. The isosteric heat of sorption measures indicated that a larger amount of heat was required to remove the water from the fresh samples than from the blanched ones.

Isotermas de sorção de umidade de abóboras frescas e branqueadas termicamente foram determinadas em três temperaturas (30, 50 e 70 °C), utilizando o método estático gravimétrico padrão. Os modelos de GAB, Oswin, BET, Halsey e Henderson foram testados e, com exceção do modelo de Henderson, mostraram ajuste satisfatório aos dados experimentais. O modelo de GAB foi usado para analisar a habilidade do ajuste na descrição do tipo de isoterma. A forma das isotermas de dessorção de abóbora fresca e branqueada determinadas a 30 e 50 °C foi intermediária aos tipos II e III e a 70 °C foi do tipo II para abóbora branqueada e próxima ao tipo II para abóbora fresca. A influência do branqueamento sobre a redução da umidade de equilíbrio das amostras foi muito pequena em comparação com amostras frescas e foi relacionada à perda de sólidos solúveis durante o pré-tratamento. Os valores de calor isostérico de sorção para tecido de abóbora indicaram que maior calor foi requerido para remover água das amostras frescas do que das amostras branqueadas.
Isotermas de sorção de umidade de abóbora (Cucurbita moschata) fresca e branqueada
Keywords: Blanching; Pumpkin; desorption isotherms; isosteric heat; GAB model; branqueamento; abóbora; isotermas de dessorção; calor isostérico; modelo de GAB